KONFLIK BATIN TOKOH UTAMA NOVEL JANJI KARYA TERE LIYE DAN IMPLEMENTASINYA DALAM PEMBELAJARAN BAHASA INDONESIA - Ernisa Prastiwi; Titik Sudiatmi; Suparmin Suparmin (Universitas Negeri Makassar, 2024)
This study aims to describe the form of inner conflict in the main character and the implementation of Indonesian language learning in Junior High School. This type of research is descriptive-qualitative, which produces sentence and dialogue data. Data collection techniques were carried out through reading, marking, and recording techniques. The research data was analyzed using qualitative descriptive data analysis techniques. The results showed that the inner conflict of the main character includes anxiety, doubt, and sadness. sadness, doubt, and anxiety in the main character that cannot be expressed. The id character of the main character is to do whatever he wants, even though it is very disturbing to people, as a balance to the deeds done by praying. Meanwhile, the form of his superego is that Bahar is willing to surrender himself to the police as the perpetrator of the main market arson, even though it was not his doing. The implementation of the main character's inner conflict in Indonesian language learning in high school is used as teaching material for teaching class XII literature in Indonesian language high school, according to KD 3.9, which analyzes the content and language of novels.